Trade beads of Furayḥah. Evidence of trade and connections of Qatar in the eighteenth and nineteenth centuries from a small-finds perspective - Andersson, Ann (Proceedings of the Seminar for Arabian Studies, 2016)
Beads belong to a small-finds object class; they are easily transportable, and can be traded over vast distances and therefore they can be useful to indicate long-distance trade and contacts. Beads are often overlooked as they are largely invisible in historical sources relating to the Gulf. As a result, their potential as signifiers of trade may well go unnoticed if they are classified solely as personal adornments. This study focuses on the bead assemblage excavated at Furayhah, a settlement located near the larger trading port, al-Zubārah, in north-western Qatar. The results of the preliminary study of the Furayḥah beads have revealed a high percentage of European trade beads at the site. The identified trade beads provide clues to networks of commerce and the varied connections enjoyed by the settlement during the eighteenth and nineteenth centuries AD, and add information on the complex webs of interaction in the Gulf area at this time.